FEATURES OF THE DEVELOPMENT STRATEGY OF THE HOSPITALITY INDUSTRY IN MODERN CONDITIONS - Victoria Kolesnyk; Valentine Polupan; Natalia Penkina; Svetlana Sorokina; Victoria Akmen (Scientific Journal of Polonia University, 2024)
The hotel business is one of the key elements of modern entrepreneurship, especially significant in the context of expanding the territorial framework of business, political, and scientific communications; development of sports and tourism, as well as improving the quality of life of the population. The hotel business, both in domestic and international practice, is a promising and rapidly evolving field of entrepreneurial activity, which concentrates a significant potential for development both at the local and international level, capable of bringing stable income. It has been proven that the management strategy of hotel enterprises is designed to ensure economic growth in the conditions of uncertainty of the socio-economic development of the hotel industry, significant innovative changes, expand the horizons of prediction and thereby create the possibility of a timely response of the hotel industry enterprise to those changes that occur in the external environment. It has been established that each of the types of management of a hotel enterprise differs from each other not only in terms of the implementation of its main functions (planning, regulation, forecasting, organization, control, accounting and analysis), as well as in the detailing or consolidation of the implementation of economic, financial, organizational and social indicators, but also, being in a single management system, should be equally focused on achieving the main goal – obtaining the greatest result in the form of hotel and related services with rational use of labor, material, technical and financial resources.